Effect of Carbon Nanofiber on Mechanical Behavior of Asphalt Concrete - Ghaffarpour Jahromi, Saeed (International Journal of Sustainable Construction Engineering and Technology, 2015)
Uses of fibers to improve material properties have a scientific background in recent years in civil engineering. Use of Nanofiber reinforcement of materials refers to incorporating materials with desired properties within some other materials lacking those properties. Use of fibers for improvement is not a new phenomenon as the technique of fiber-reinforced bitumen began as early as 1950, but using nanofiber is a new idea. In this research the mechanical properties of asphalt mixture that have been modified with carbon nanofiber were investigated using mechanical tests, which can improve the performance of flexible pavements. To evaluate the effect of nanofiber contents on bituminous mixtures, laboratory investigations were carried out on the samples with and without nanofibers. During the course of this study, various tests were undertaken applying the Marshall test, indirect tensile test, resistance to fatigue cracking by using repeated load indirect tensile test and creep test. Carbon nanofiber exhibited consistency in results and it was observed that the addition of nanofiber can change the properties of bituminous mixtures, increase its stability and decrease the flow value. Results indicate that nanofiber have the potential to resist structural distress in the pavement and thus improve fatigue by increasing resistance to cracks or permanent deformation, when growing traffic loads. On the whole, the results show that the addition of carbon nanofiber will improve some of the mechanical properties such as fatigue and deformation in the flexible pavement.